2022
DOI: 10.1007/s40472-022-00357-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Solid Organ Transplantation: Role of Anti-SARS-CoV-2 Monoclonal Antibodies

Abstract: Purpose of Review Solid organ transplant recipients (SOTRs) are ideal candidates for early treatment or prevention of coronavirus disease 2019 (COVID-19) using anti-SARS-CoV-2 monoclonal antibodies because of multiple underlying medical conditions, chronic immune-suppression, sub-optimal immunogenic response to vaccination, and evolving epidemiological risks. In this article, we review pertinent challenges regarding the management of COVID-19 in SOTRs, describe the role of active and passive immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Although the original clinical trials of these agents did not include many immunocompromised patients, it is likely that this group benefits the most from mAb therapy, given their immunocompromise and suboptimal responses to COVID vaccines. 11 Retrospective studie summarized below suggest that mAb treatment in SOT recipients is associated with reduced risk of hospitalization, reduced likelihood of progression to severe infection, and probably reduced mortality. 11 However, with the constantly evolving landscape of the pandemic, and a succession of new dominant variants, the utility of each monoclonal has changed over time.…”
Section: Sars-cov-2 Monoclonal Antibodies For Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the original clinical trials of these agents did not include many immunocompromised patients, it is likely that this group benefits the most from mAb therapy, given their immunocompromise and suboptimal responses to COVID vaccines. 11 Retrospective studie summarized below suggest that mAb treatment in SOT recipients is associated with reduced risk of hospitalization, reduced likelihood of progression to severe infection, and probably reduced mortality. 11 However, with the constantly evolving landscape of the pandemic, and a succession of new dominant variants, the utility of each monoclonal has changed over time.…”
Section: Sars-cov-2 Monoclonal Antibodies For Treatmentmentioning
confidence: 99%
“… 11 Retrospective studie summarized below suggest that mAb treatment in SOT recipients is associated with reduced risk of hospitalization, reduced likelihood of progression to severe infection, and probably reduced mortality. 11 However, with the constantly evolving landscape of the pandemic, and a succession of new dominant variants, the utility of each monoclonal has changed over time. For example, bamlanivimab was originally administered by itself, then later when it was no longer effective as a single agent, was given together with etesevimab, and ultimately was not used at all.…”
Section: Sars-cov-2 Monoclonal Antibodies For Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Early use of anti–severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) monoclonal antibody in SOTRs provides a safe outpatient treatment option to reduce COVID-19–related risk of hospitalization and death. 2 Sotrovimab is a recombinant human immunoglobulin-G1-kappa monoclonal antibody that binds to a conserved epitope on the spike protein receptor-binding domain of SARS-CoV and SARS-CoV-2. Sotrovimab contains a 2 amino acid Fc-modification that is designed to improve bioavailability in the respiratory mucosa and increase half-life with a projected human median elimination half-life of 49 d. 3 Based on clinical studies, in which immunocompromised patients were excluded, it received Emergency Use Authorization by the Food and Drug Administration for the treatment of mild to moderate COVID-19 in May 2021.…”
mentioning
confidence: 99%
“…The subcutaneous administration of casivirimab-imdevimab (REGEN-COV) was shown to prevent COVID-19 in previously uninfected household contacts in the general population, and, therefore, might be of importance in the prevention of COVID-19 [ 96 ]. A study by Dhand et al evaluated 25 COVID-19-infected SOT recipients receiving REGEN-COV, and demonstrated neither COVID-19 progressions nor hospitalizations in the study participants [ 97 ]. Nevertheless, observational studies evaluating the pre-exposure prophylactic administration of mAbs in LuTx recipients are awaited.…”
Section: Sars-cov-2-infected Recipient—covid-19 Treatmentmentioning
confidence: 99%